Legal Reasoning for Interfaith Marriage Case Study Yogyakarta District Court Decision Number 378/Pdt.P/2022/PNY.yk - Rizza Rohmatul Hasanah; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2023)
This journal discusses the decision of the Yogyakarta district court Number 378/Pdt.P/2022/PNY.yk in the case of interfaith marriages. The purpose of this article is to analyze the legal reasoning used by the court in deciding this case. The method used is a case study, with data collection techniques through analysis of court decision documents and related literature. The results of the analysis show that the court uses legal reasoning by considering statutory regulations, previous court decisions, as well as information and evidence presented by both parties. The court also considers the interests and welfare of the child in deciding the case. In conclusion, this article shows that the legal reasoning used by courts in deciding cases of interfaith marriages is important to understand in the context of protecting individual rights and family welfare.